The World Bank Group and Public Procurement--An Independent Evaluation : Volume 2: Achieving Development Effectiveness through Procurement in Bank Financial Assistance - Independent Evaluation Group (Washington, DC: World Bank, 2014)
Good public procurement practices are a major determinant of the effectiveness of public expenditure. On behalf of their citizens, governments typically spend as much as 5-20 percent of their gross domestic product on procurement of goods and services, and effective procurement policies enable better use of government budgets. Good national procurement practices are therefore an essential element of the poverty reduction focus of the Bank. Good procurement in Bank projects is also associated with better development outcomes. Equally, sound public procurement in client countries is a prerequisite for the success of the Bank's newly introduced program for results lending instrument. The Bank seeks to ensure that its funds are used for the purpose intended and that they support development effectively and efficiently. Thus, the twin issues that underpin this Independent Evaluation Group (IEG) evaluation are first, how effectively has the World Bank helped build well-functioning public procurement systems in client countries and second, how well have Bank procurement policies and procedures for its investment lending supported the development effectiveness of Bank lending? The evaluation parallels an intensive review by Bank management of the institution's procurement function, motivated by the need to respond to a range of internal and external changes in the Bank's procurement environment. Several evaluations point to the value of coordination between procurement and public expenditure reforms, but also to the difficulties of realizing such coordination. Finally, there are queries related to the adaptability of current Bank procurement guidelines to new contexts, such as public-private partnerships (PPPs); technology loans; and small, fragile, or conflict-affected states. These questions have also contributed to the evaluation's design and coverage.